RELATIONSHIP BETWEEN SLEEP QUALITY AND ACADEMIC STRESS WITH PREMENSTRUAL SYNDROME IN FINAL-YEAR NURSING STUDENTS - Rangkuti, Kayla Syakira; Ismail, Rita; Marcelina, Lina Ayu; Desmawati, Desmawati (Poltekkes Kemenkes Jakarta III, 2025)
Premenstrual Syndrome (PMS) is a common condition among menstruating women, often influenced by factors such as sleep quality and stress levels. Final-year female students are particularly vulnerable to sleep disturbances and academic stress. This study analyzes the relationship between sleep quality and academic stress with PMS among final-year nursing students at UPN “Veteran” Jakarta. A Cross-Sectional design was used, and data was collected in November 2024. The study involved 188 final-year students: Bachelor of Nursing (79 respondents), Diploma in Nursing (45 respondents), and Professional Nurse Education Program (64 respondents), selected through Stratified Convenience Sampling. Pittsburgh Sleep Quality Index (PSQI), Student-Life Stress Inventory (SLSI), and Shortened Premenstrual Assessment Form (SPAF) were used to measure sleep quality, academic stress, and PMS. Data were collected via online questionnaires and analyzed using the chi-square test. Results revealed a significant relationship between sleep quality (p = 0.000; OR = 5,989) and academic stress (p = 0.000; OR = 28,761) with PMS. Students with poor sleep quality had a 6-fold higher risk of severe PMS, while those with high academic stress had a 29-fold higher risk. This study emphasizes the importance of maintaining healthy lifestyles, such as improving time management to enhance sleep quality and adopting coping strategies to reduce academic stress, thereby minimizing PMS complaints